Long-term changes in soil aggregation comparing forest and agricultural land use in different Mediterranean soil types - Chrenková, Katarína; Mataix-Solera, Jorge; Dlapa, Pavel; Arcenegui, Victoria (Geoderma, 2014)
The formation and stabilization of soil aggregates have a key role to play in adequate soil functioning. Aggregate stability (AS) is considered by some authors to be a property that provides information on soil quality. It's also a property that is highly influenced by land use and management. This study aims to identify the long-term changes in soil aggregation and related properties comparing forest and agricultural land use in Mediterranean calcareous soils. For the research, seven study sites with different soil characteristics located in Alicante Province (E Spain) were chosen to compare the overall effect of land use change from agriculture to forestry on soil aggregation. At every site, samples of the same soil type were collected from agricultural land (dry crops with conventional tillage management using ploughing), and nearby forest, where agriculture was abandoned between 20 and 50years ago. Selected physical and chemical properties like: texture, total content of aggregates (TCA), aggregate stability (AS), organic matter content (OM), carbonates, mean weight diameter (MWD) of aggregates and water repellency (WR) were analysed on the collected soil samples. As expected, in all soils, the AS was significantly lower in agricultural sites than in forest sites. But in some cases the differences were much higher than in others. In forest sites the AS varied between 46 and 82% while in agricultural sites it ranged between 14 and 45%. The results showed strong positive correlation of AS with OM. The lowest values of AS in forest areas were found in wettable sandy soils. The relative increase of AS in forest soils compared to agricultural land use ranged from 39 to 79%. These differences can be explained mainly by some soil properties, such as OM content, texture, and WR. In particular, the lower OM content and absence of WR are responsible for the lower values of AS in agricultural land use due to the long-term conventional tillage management. Soil WR was found in three of the sites, and its presence plays a key role in soil aggregation and its stability, especially for sandy soils. The MWD was in most cases higher in forest than in agricultural sites, except for two wettable sandy soils with the lowest initial AS. In the case of carbonates, no correlations were found with AS, and only in the group of sandy soils, significant positive correlations between carbonates and TCA and with MWD were found. In conclusion we can say that the prolonged use of conventional tillage management using ploughing has a strong influence on AS in all types of soils studied in this research. The recovery after decades of land use abandonment not only is dependent on how is the increase of soil OM content, but also is controlled by some soil properties such as the texture and the presence of WR. In some cases the presence of hydrophobic substances can play a key role in the formation and stabilization of soil aggregates, contributing to maintaining good levels of OM and avoiding higher levels of soil degradation.
Keywords: Aggregate stability; Conventional tillage; Mean weight diameter; water repellency

Effects of a low severity prescribed fire on water-soluble elements in ash from a cork oak (Quercus suber) forest located in the northeast of the Iberian Peninsula. - Pereira, Paulo; Úbeda, Xavier; Martin, Deborah; Mataix-Solera, Jorge; Guerrero, César (Environmental research, 2011)
Wildfire is the major disturbance in Mediterranean forests. Prescribed fire can be an alternative to reduce the amount of fuel and hence decrease the wildfire risk. However the effects of prescribed fire must be studied, especially on ash properties, because ash is an important nutrient source for ecosystem recovery. The aim of this study is to determine the effects of a low severity prescribed fire on water-soluble elements in ash including pH, electrical conductivity (EC), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), aluminum (Al), manganese (Mn), iron (Fe), zinc (Zn), silica (SiO(2)) and total sulphur (TS). A prescribed fire was conducted in a cork oak (Quercus suber) (Q.S) forest located in the northeast part of the Iberian Peninsula. Samples were collected from a flat plot of 40×70m mainly composed of Q.S and Quercus robur (Q.R) trees. In order to understand the effects of the prescribed fire on the soluble elements in ash, we conducted our data analysis on three data groups: all samples, only Q.S samples and only Q.R samples. All three sample groups exhibited a significant increase in pH, EC (p<0.001), water-soluble Ca, Mg, Na, SiO(2) and TS and a decrease in water-soluble Mn, Fe and Zn. Differences were identified between oak species for water-soluble K, Al and Fe. In Q.S samples we registered a significant increase in the first two elements p<0.001 and p<0.01, respectively, and a non-significant impact in the third, at p<0.05. In Q.R data we identified a non-significant impact on water-soluble K and Al and a significant decrease in water-soluble Fe (p<0.05). These differences are probably due to vegetation characteristics and burn severity. The fire induced a higher variability in the ash soluble elements, especially in Q.S samples, that at some points burned with higher severity. The increase of pH, EC, Ca, Mg, Na and K will improve soil fertility, mainly in the study area where soils are acidic. The application of this low severity prescribed fire will improve soil nutrient status without causing soil degradation and thus is considered to be a good management strategy.
Keywords: Ash; iberian peninsula; Prescribed fire; Quercus robur; Quercus suber